A SUSTAINABLE APPROACH TO THE CONTROL OF PATHOGENS: THE FATE OF STREPTOCOCCI IN EQUINE COMPOST. - Poulin, Alexandria; Mitchell, Scott D; Myer, Ashlie; Harvey, Kathleen; Hutchinson, Mark; Causey, Robert (European Scientific Journal, ESJ, 2015)
Streptococcus equi subspecies equi (S. equi), causes the potentially fatal respiratory disease called “strangles” in horses, while the closely related Streptococcus equi subspecies zooepidemicus (S. zooepidemicus) causes potentially fatal infections in humans. A study was undertaken to determine the survival of these two organisms in equine compost. Compost piles of equine bedding and feed waste were inoculated with 10 x 1010 c.f.u. of S. zooepidemicus and samples taken at 48, 96, 168 and 336 hours relative to samples placed in the pile at 0 hours. No Streptococci were isolated at 48 hours or subsequent time-points. Next, S. equi was similarly inoculated into equine compost, with samples taken at 2, 4, 8, 12, 24, 48, 168 and 336 hours later. No Streptococci were isolated at any time-point. To rule out killing of S. equi by microflora in equine waste, samples of soiled bedding, both autoclaved and un-autoclaved (with water added to match autoclaved moisture) were inoculated with 10 x 1010 c.f.u. of S. zooepidemicus and sampled at 0, 6, 12, 24, 48, 72, 120, 168 and 264 hours. In autoclaved bedding, S. zooepidemicus was isolated from 0 – 120 hours, but replaced by other flora at 264 hours. In un-autoclaved samples, Streptococci were not present after 48 hours. A repeated trial with S. equi yielded similar results. This data suggest that microbial activity of equine waste bedding may eliminate streptococci within 24 - 48 hours, indicating that normal microflora may provide sustainable methods for the control of human and animal pathogens.